Synthesis and Application of Some Bisazo Acid Dyes Based on 4-Hydroxy quinoline Quinazoline System on Various Fabric - Patel, N.C.; Mehta, A.G. (Asian Journal of Chemistry, 2010)
Fifteen 3-(4' -R-azo-1 '-phenylazo )-4-hydroxy quinolino-[1,2-b]- 4-oxoquinazolines (IVa-o) were prepared by coupling diazotised 3-(4' -amino-1' -phenylazo )-4-hydroxy quinolino-[ 1,2-b ]-4-oxoquinazoline (III) with various coupling components (a-o). The compound (I) was coupled with diazotised p-arninoacetanilide giving compound II, which on hydrolysis gave compound III. The compounds IVa-o were characterised by elemental and spectral analyses and their dyeing performance on silk, wool and nylon fabrics was assessed.